Analisis Komparatif Kepuasan Bermain dan Implikasi Biomekanik pada Pemain Bulutangkis: Studi Perbandingan Antara Lapangan Karpet Sintetis Versus Lantai Semen - Tendy Roy; Eri Barlian; Donie; Tjung Hauw Sin; Anton Komaini; Sepriadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to comprehensively examine the difference in playing satisfaction between synthetic carpet courts (vinyl/PVC) and cement floor courts (concrete) among badminton players, while also analyzing the underlying biomechanical implications. This quantitative study, using an ex-post facto approach, involved 150 badminton players (98 men, 52 women, aged 18-35 years). The results of the Paired Sample t-Test showed a statistically highly significant difference (t = 24.83; p = 0.000 < 0.05). The mean playing satisfaction score on synthetic carpet courts (M = 4.32; SD = 0.45) was significantly higher than on cement floor courts (M = 2.85; SD = 0.58). Shock absorption and pain prevention emerged as the largest contributors to the higher satisfaction level on carpet courts. These findings indicate the need for a gradual conversion of badminton court surfaces from cement floors to BWF-standard synthetic carpet to improve playing comfort and reduce players' risk of biomechanical injury. Keywords: Sports Biomechanics, Badminton, Synthetic Carpet, Playing Satisfaction, Cement Floor